Severe sepsis caused by Capnocytophaga canimorsus complicated by thrombotic microangiopathy in an immunocompetent patient. Issue 1 (23rd May 2016) - Maezawa, Shota; Kudo, Daisuke; Asanuma, Keiichiro; Takekoshi, Daisuke; Egashira, Ryuichiro; Kushimoto, Shigeki
Abstract : Case: A 61‐year‐old man with an unremarkable medical history was admitted with fever 7 days after being bitten by his dog. On day 3, he showed altered mental status, and laboratory data showed progressive hemolytic anemia, thrombocytopenia, hyperbilirubinemia, renal dysfunction, coagulopathy, and schistocytosis. Severe sepsis complicated with thrombotic microangiopathy caused by Capnocytophaga canimorsus was suspected. Outcome: Plasma exchange was applied to treat the thrombotic microangiopathy and resulted in platelet count increase and improved renal function, hyperbilirubinemia, and schistocytosis. Blood culture results confirmed the presence of C. canimorsus . The patient was discharged in good condition. Conclusion: Capnocytophaga canimorsus is rare cause of severe sepsis, and should be suspected even in immunocompetent patients with dog‐bite history. Capnocytophaga canimorsus infection may be complicated by thrombotic microangiopathy, for which plasma exchange should be considered prior to definitive diagnosis of thrombotic microangiopathy.